Desarrollo de una propuesta de implementación del sistema de buenas prácticas de manufactura (BPM), en la empresa de lácteos PROLASE (productos lácteos San Enrique) en la parroquia de Mulaló. - Carrillo Pérez, Erik Fabricio (2021)
In this integrative Project, a proposal for the implementation of the system of good manufacturing practices (GMP) was raised, in this research was taken as a reference the Sanitary Technical Standard For Processed Food Resolution 067 Official Register Supplement 681 of 01/feb/2016, Last modification on 11/may/2017 Status: Reformed No. ARCSA-DE-067-2015-GGG, which for the evaluation was used instruments such as direct observation and a checklist was developed where 8 items were covered which are: facilities, equipment and utensils, hygienic manufacturing, raw materials and inputs, production operations, packaging, labeling and packaging, storage, distribution and transportation, quality assurance and control, where it was obtained as results that 68. 48% complies with the requirements of regulation 067, 25.25% does not comply and finally 6. 27% do not apply, which is why the results obtained preceded the fulfillment of the objectives set out in which the documentation was prepared that will allow the improvement of production in the company, all based on standard operating procedures (SOP), standard operating procedures for sanitation (SSOP), specifically in GMP parameters, For this reason, documentation was proposed with measures that will help prevent and correct errors, For these improvements, a financial technical study was carried out which determined a total investment of 12,428.83 USD, The manager or owner of the company can make use of this documentation and implement it when economic resources permit.